Anticancer Molecular Mechanisms of Resveratrol - Varoni, Elena M. (Front Nutr, 2016)
Resveratrol is a pleiotropic phytochemical belonging to the stilbene family. Though it is only significantly present in grape products, a huge amount of preclinical studies investigated its anticancer properties in a plethora of cellular and animal models. Molecular mechanisms of resveratrol involved signaling pathways related to extracellular growth factors and receptor tyrosine kinases; formation of multiprotein complexes and cell metabolism; cell proliferation and genome instability; cytoplasmic tyrosine kinase signaling (cytokine, integrin, and developmental pathways); signal transduction by the transforming growth factor-β super-family; apoptosis and inflammation; and immune surveillance and hormone signaling. Resveratrol also showed a promising role to counteract multidrug resistance: in adjuvant therapy, associated with 5-fluoruracyl and cisplatin, resveratrol had additive and/or synergistic effects increasing the chemosensitization of cancer cells. Resveratrol, by acting on diverse mechanisms simultaneously, has been emphasized as a promising, multi-target, anticancer agent, relevant in both cancer prevention and treatment.